Mobile banking in Iceland the behaviour and views of managers and consumers - Laufey Fríða Guðmundsdóttir 1984- (2019)
The constant evolution in wireless technology and smartphone services has encouraged banks and financial institutions to implement mobile banking in their services. However, a substantial number of consumers have yet to adopt this new technology. The objective of this thesis is to assess which factors influence consumer behaviour regarding adoption of mobile banking in the consumer market. In addition, the behaviour of managers in financial institutions providing mobile banking services was analysed. The thesis is based on the theoretical model named: The Marketing Firm by Gordon Foxall. The research is derived from two separate studies; the first study is a questionnaire-based survey on the use of mobile banking services in a population of Icelandic bank consumers (N = 485). The second study is built on a number of semi- structured interviews with current managers in the mobile banking sector in Iceland. The aim was to determine which factors most strongly affect consumer behaviour when adopting a mobile banking application. The findings showed that higher education and higher income had the largest effect on the probability of non-users adapting to mobile banking in the future. However, the gender and age of non-users had no effect on their responses. Furthermore, the perceived trustworthiness of the provider, and the interest in an educational course on mobile banking apps was positively related to consumer willingness to adopt mobile banking. Users generally approved of mobile banking services and their beneficial impact on their daily business. According to responses from consumers and managers, mobile banking services are beneficial for both parties. Hopefully the findings will encourage mobile banking suppliers in both the development and improvement of their services in order to further increase the quality of mobile banking in Iceland.